Potret pendidikan pemakai selama pandemi Covid-19: Studi kasus pada UPT Perpustakaan dan Universitas Diponegoro Press - Nabilla Layza Nugroho; Roro Isyawati Permata Ganggi (Jurnal Ilmu Perpustakaan, 2025)
[Title: a Portrait of User Education During The Covid-19 Pandemic: A Case Study Of Technical Executive Unit Library and Press Universitas Diponegoro] The background of this research is that sometimes there are students who know where to find the right reference for their assignment, and there are students who have problems finding references. Therefore, the Technical Executive Unit Library and Press Universitas Diponegoro organized a "Library Tour" user education program. The library tour aims to provide library systematics education to new students of Universitas Diponegoro every new academic year. Since the COVID-19 pandemic, the library tour has been held through webinars. This study aimed to determine the implementation of user education at the Technical Executive Unit Library and Press Universitas Diponegoro during the COVID-19 pandemic. The method used is qualitative with Miles and Huberman analysis, namely data reduction, data presentation, and conclusions. Observation, interviews, and documentation studies carry out data collection techniques. The selection of informants is carried out. The selection of informants is carried out by purposive sampling. The result of this research is that the implementation of user education at the Technical Executive Unit Library and Press Universitas Diponegoro during the COVID-19 pandemic was carried out using online webinars. This webinar was conducted to deliver material about the services provided by the Technical Executive Unit Library and Press Universitas Diponegoro and introduce the library as a whole. The webinar was conducted using Zoom Meeting as a media library tour, and the entire seminar was conducted as a webinar using a lecture method. The advantage of the webinar library tour is that it is effective and flexible, while the disadvantage is that there is limited interaction. Regarding its effectiveness, library tour webinars that use the lecture method are quite effective because students get theories from the library about various important information and knowledge such as that reservoir services and reference services can only be read on the spot and cannot be borrowed. Webinar material can be said to be representative and useful because students use the material introduced during the webinar in their daily lives.